THE DADER METHOD FOR PHARMACOTHERAPY FOLLOW-UP AND PHARMACOVIGILANCE IN HEALTH INSTITUTIONS OF COLOMBIA - Pedro AMARILES M. (Universidad de Antioquia, 2009)
The Pharmacovigilance pretends to satisfy the need of information related to the results of pharmacotherapy, at the same time, it turns into a tool for preventing risks and decreasing costs caused by the undesired effects of the pharmacotherapy. In Colombia, the DADER method for drug therapy follow-up has shown that it is possible to accomplish with the goals of pharmacovigilance. However, more support is required about the utility and benefits achieved with its implementation in a larger number of health institutions. In this sense, a retrospective descriptive study of the results of drug therapy follow-up by the Dader method, it is carried out both at ambulatory health institutions and at hospital health institutions, by students of the Pharmacy program, at the University of Antioquia, who participated in the courses of clinical pharmacy practices or professional practices, from august 2003 to november 2004. During this period: 4.556 patients were followed and 660 problems related to drugs and 3.581 problems related to the use of drugs were detected. These results confirm the usefulness and additional benefits of the drug therapy follow-up of patients by the DADER method, about the fulfillment of the necessity to arrange and to expand pharmacovigilance programs in the Colombia Health System.